Late Holocene Pollen Record of Environmental Changes in Karimata Strait, Sunda Shelf Region - Eko Yulianto; Woro Sri Sukapti; Kresna Tri Dewi (Geological Agency, 2019)
DOI: 10.17014/ijog.6.1.41-55Pollen analysis has been conducted on a 90 cm gravity core taken from the Karimata Strait to reveal pollen facies in marine sediment and Late Holocene environmental changes in the central Sunda Shelf region. The core site is at 32 m water depth and located about 170 km northwest of Bangka Island, Indonesia. Ten samples were collected at 10 cm intervals through the core. The total number of pollen grains counted in the samples varies between very low (<50 grains) to abundant (>200 grains). High frequencies (50 - 70%) of mangrove pollen are found at 90 to 40 cm indicating that pollen facies in offshore marine sediment may be comparable with those in mangrove forest floor sediment. The core site has been in a neritic environment since its early deposition ca. 1,800 yr B.P. ( 150 A.D.) when mangroves vastly grew on the tidal flats of the surrounding islands and they persisted to ca. 700 yr B.P. ( 1,250 A.D.). In the middle of this period, a catastrophic event speculatively due to the 535 A.D. Krakatau eruption might have responsible for the decrease of mangroves and the disappearance of benthic foraminifers. The deposition of silicious materials (tephra) due to this eruption might have provided an opportunity for benthic foraminifers to increase their population subsequently. From ca. 700 yr B.P. ( 1,250 A.D.) mangroves declined, as indicated by lower frequencies of pollen grain in samples from 30 cm deep upward. It occurred simultaneously with the deposition of coarser sediment and the increase of benthic foraminifer abundance. Interplay of anthropogenic activities, strengthening ENSO cycle, and lowering erosion base level might have been responsible for these environmental changes.